IOU field reports form, Douglas C. Harr, December 1, 1995 - Harr, Douglas C.et al (1995)
List of birds and locations contributed by Douglas C. Harr. Also includes details on a Tundra Swan observed by Craig Van Otterloo. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1995. Epson - sheet feed/flatbed